2021
DOI: 10.1101/2021.07.30.454422
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Species hybridisation and clonal expansion as a new fungicide resistance evolutionary mechanism in Pyrenophora teres spp

Abstract: The barley net blotch diseases are caused by two fungal species of the Pyrenophora genus. Specifically, spot form net blotch is caused by P. teres f. sp. maculata (Ptm) whereas net form net blotch is caused by P. teres f. sp. teres (Ptt). Ptt and Ptm show high genetic diversity in the field due to intraspecific sexual recombination and hybridisation of the two species although the latter is considered rare. Here we present occurrence of a natural Ptt/Ptm hybrid with azole fungicides resistance and its implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…However, most of the progeny isolates showed spot-like disease symptoms and only 13 of the progeny isolates could be clearly identified as having net-like symptoms. Similar observation was made for field collected hybrids which also all showed spot-like disease symptoms ( Campbell et al, 2002 ; Mclean et al, 2014 ; Turo et al, 2021 ). Spot- and net-form symptoms are impossible to differentiate at the lower infection rates and thus, some of these progeny isolates could have been miss-classified as spot-form instead of net-form.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, most of the progeny isolates showed spot-like disease symptoms and only 13 of the progeny isolates could be clearly identified as having net-like symptoms. Similar observation was made for field collected hybrids which also all showed spot-like disease symptoms ( Campbell et al, 2002 ; Mclean et al, 2014 ; Turo et al, 2021 ). Spot- and net-form symptoms are impossible to differentiate at the lower infection rates and thus, some of these progeny isolates could have been miss-classified as spot-form instead of net-form.…”
Section: Discussionsupporting
confidence: 80%
“…To the author’s knowledge, this is the first study to use a hybrid population of Pyrenophora teres f. teres and Pyrenophora teres f. maculata in a QTL analysis study. Recent identification of an increasing number of hybrids in barley fields indicates the importance of understanding the virulence patterns of hybrid isolates ( Turo et al, 2021 ). The results of this study give an insight into the virulence profile of hybrid isolates with respect to their parental isolates and provide useful information about barley- P. teres pathosystem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low number of clones in these MLGs (11) provides weak evidence for recent selection of beneficial genotypes, perhaps masked by susceptible popular cvs. For example, predominantly clonal Ptm isolates were previously found in cv Oxford in southern WA, associated with a virulent new pathotype in combination with demethylase inhibitor (DMI) fungicide resistance ( Turo et al . 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pyrenophora teres form teres (Ptt) produces net-like lesions while P. teres f. maculata (Ptm) causes brown spots surrounded by chlorosis, thus referred to as 'net form net blotch' and 'spot form net blotch' , respectively. Ptt and Ptm cross easily in lab conditions [34], their artificial hybrids are fertile [35], and they can produce clonal hybrid lineages in the field [36]. However, population genomic studies revealed neither pervasive admixture nor rampant gene flow [37][38][39][40], which suggests that ecologically-based reproductive barriers contribute to the maintenance of Ptt and Ptm in sympatry on the same host [41].…”
Section: Introductionmentioning
confidence: 99%